2002
DOI: 10.1038/nn814
|View full text |Cite
|
Sign up to set email alerts
|

Humans and great apes share a large frontal cortex

Abstract: Some of the outstanding cognitive capabilities of humans are commonly attributed to a disproportionate enlargement of the human frontal lobe during evolution. This claim is based primarily on comparisons between the brains of humans and of other primates, to the exclusion of most great apes. We compared the relative size of the frontal cortices in living specimens of several primate species, including all extant hominoids, using magnetic resonance imaging. Human frontal cortices were not disproportionately lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
270
3
6

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 476 publications
(290 citation statements)
references
References 22 publications
11
270
3
6
Order By: Relevance
“…The present analysis extends this observation of predictability both to non-primates and to the total visual cortex devoted to visual analysis. Primary visual cortex scales at a rate higher than other primary sensory areas, but lower, for example, than prefrontal cortex (see below), which scales with steep 'positive allometry', occupying a predictably and proportionately larger component of total cortical volume ( Jerison 1997;Semendeferi et al 2002). Parietal cortex, containing many of the areas included in our 'total visual cortex' sample also scales steeply with brain size.…”
Section: (I) Rods and Conesmentioning
confidence: 93%
“…The present analysis extends this observation of predictability both to non-primates and to the total visual cortex devoted to visual analysis. Primary visual cortex scales at a rate higher than other primary sensory areas, but lower, for example, than prefrontal cortex (see below), which scales with steep 'positive allometry', occupying a predictably and proportionately larger component of total cortical volume ( Jerison 1997;Semendeferi et al 2002). Parietal cortex, containing many of the areas included in our 'total visual cortex' sample also scales steeply with brain size.…”
Section: (I) Rods and Conesmentioning
confidence: 93%
“…(1) is a particularly elegant example of a growing body of evidence for this conclusion. For instance, several studies have shown that the human frontal cortex occupies the same proportion of total cortex in humans as it does in great apes (10,11). Therefore, humans are typical primates with regard to the portion of their cortex devoted to frontal cortex.…”
Section: Implications For Neurobiological Continuitymentioning
confidence: 99%
“…The extensive scope of myelination is the single-most unique aspect in which the human brain differs from that of other species [1][2][3]. In this myelin model of human evolution and development, our brain's extensive myelination accounts for the high processing speeds and precise temporal coding underlying higher cognitive and behavioral functions [4,5].…”
Section: Introductionmentioning
confidence: 99%